Design of a fluorescent and clickable Ag38(SRN3)24 nanocluster platform: synthesis, modeling and self-assembling. Issue 10 (15th April 2021) - Campi, Gaetano; Suber, Lorenza; Righi, Giuliana; Primitivo, Ludovica; De Angelis, Martina; Caschera, Daniela; Pilloni, Luciano; Del Giudice, Alessandra; Palma, Amedeo; Satta, Mauro; Fortunelli, Alessandro; Sementa, Luca
Abstract : Fluorescent Ag38 (SRN3 )24 nanoclusters with the novel presence of terminal azido groups for easily "click"-binding a wide set of molecular species and their self-assembling in lamellar and hexagonal superstructures permeated by nanoregion defects. Abstract : Fluorescent atomically precise Ag38 (11-azido-2-ol-undecane-thiolate)24 nanoclusters are easily prepared using sodium ascorbate as a "green" reducer and are extensively characterized by way of elemental analyses, ATR-FTIR, XRD, SAXS, UV-vis, fluorescence spectroscopies, and theoretical modeling. The fluorescence and the atomically determined stoichiometry and structure, the facile and environmentally green synthesis, together with the novel presence of terminal azido groups in the ligands which opens the way to "click"-binding a wide set of molecular species, make Ag38 (11-azido-2-ol-undecane-thiolate)24 nanoclusters uniquely appealing systems for biosensing, recognition and functionalization in biomedicine applications and in catalysis.